Age and Depositional Environment of Whale-Bearing Sedimentary Succession from the Lower Pliocene of Tuscany (Italy): Insights from Palaeomagnetism, Calcareous Microfossils and Facies Analyses - Marini, M.; Foresi, L. M.; Barbagallo, V.; Bisconti, M.; Di Stefano, A.; Muttoni, G.; Martini, I. (Journal of Marine Science and Engineering, 2023)
A c. 31 m thick section straddling the fossil find of an Early Pliocene baleen whale ("Brunella", hereafter), made in 2007 in the sedimentary fill of the Middle Ombrone Basin of Tuscany, is investigated for depositional age and environment combining palaeomagnetic, micropalaeontological (Foraminifera and calcareous nannofossils) and sedimentary facies analyses. Resting unconformably onto Late Miocene continental deposits, the Early Pliocene marine deposits include, from bottom to top, a coarse-grained wave-winnowing lag, the few metres-thick fossiliferous sandstone bedset from which Brunella was unearthed, and several metres of clays. The stratigraphic organisation of these deposits indicate deposition in a deepening upward inner shelf environment. Successful isolation of characteristic remanent magnetisation and calcareous nannofossil content indicate the investigated marine section was deposited during the interval of polarity Chron C3n.2n corresponding to the basal part of the Mediterranean nannofossil zone MNN13 (between Helicosphaera sellii Base common and the Amaurolithus primus Top) and allow estimating the depositional age of Brunella to c. 4.6 Ma. Sedimentary facies, benthic Foraminifera association and anisotropy of magnetic susceptibility characterising the deposits that embedded Brunella suggest deposition above the fair-weather base level.